The Heidelberg Catechism on prayer: relevance of a 16th Century confession for 21st Century households? - E. Mouton (Acta Theologica)
In a world characterized by power abuse and violence, where and how would people with the life-affirming ethos of God’s alternative kingdom be formed? In view of this challenge, the essay explores the potential of the third part of the Heidelberg Catechism (on prayer) for moral formation in Christian households. It is believed that, through facilitating transformative encounters with the living God, the Catechism holds the potential also to shape (young) people’s imagination and behaviour in present-day (African) contexts, provided that a critical-constructive awareness of the hierarchical origins of New Testament household codes be nurtured alongside it.